Analysis on carbon footprint: A case study of Gorkhapatra national daily in Nepal - Sharma, Anukram; Poudyal, Khem N; Bhattarai, Nawraj (Journal of Innovations in Engineering Education, 2021)
Study of carbon footprint is an emerging field which provides statistical analysis about the contribution of an activity on global climate change. Every human activity in daily life is achieved at the expense of those substances which directly or indirectly contribute to global warming. In this era of global communication, humans are habitual to know about the ongoing changes in the world. Newspapers are one of the reliable sources for getting updated about the global information. Paper-based newspapers come at the cost of greenhouse gas emissions. So, this article based upon an analysis of carbon footprint of Nepal’s national daily newspaper provides evaluation of each of the following: carbon emission during the manufacturing of raw materials, carbon emission from fuel consumption during transportation of raw materials, carbon emissions during the printing of newspaper and carbon emission from the fuel consumption during the transportation of printed newspaper. During the study period of 2019 A.D., the result shows that the total carbon emission of Gorkhapatra newspaper was found to be 2308.5 kg CO2e per ton. The upshot of this study provides not only thorough information about carbon emissions but also builds a foundation for calculation of carbon emissions from paper used in various sectors.